2021
DOI: 10.1155/2021/7512957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hafnium Coating on Osseointegration of Titanium Implants: A Split Mouth Animal Study

Abstract: The behaviour of hafnium as surface coating in biological environments has not been studied. Little is known about osseointegration of hafnium-coated titanium implants. Thus, further studies of hafnium coating under biological conditions are required in order to determine the suitability of this material, as a surface coating for biomedical application. The aim of the study is to analyse the difference between hafnium-coated titanium and uncoated titanium by evaluating the osseointegration ability of hafnium m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…However, with increasing knowledge about the biocompatible properties of pure hafnium, it was confirmed that Hf exhibits a high level of corrosion resistance and good tribocorrosion and biocompatibility [ 10 , 11 , 12 , 13 ]. Moreover, to our knowledge, Hf-containing titanium-based alloys are also widely used as medical implants [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing knowledge about the biocompatible properties of pure hafnium, it was confirmed that Hf exhibits a high level of corrosion resistance and good tribocorrosion and biocompatibility [ 10 , 11 , 12 , 13 ]. Moreover, to our knowledge, Hf-containing titanium-based alloys are also widely used as medical implants [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distinct flavour of ginger is the result of potent ketones, such as gingerol, which are largely employed in research. 17 It contains several biological properties, including antibacterial, antioxidant and anticancer properties, as well as immune system stimulating properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, unique and innovative technologies have enabled the production of controlled architecture grafts. Various studies have been done time and again to experiment on the coating of implants [ 10 , 11 ], bone substitutes, etc. Studies show promising results for alloplastic substitutes as successful bone substitutes for enhanced regenerative properties.…”
Section: Introductionmentioning
confidence: 99%